Performance evaluation of the SIMBIO-SYS Stereo Imaging Channel on board BepiColombo/ESA spacecraft. (March 2019) - Slemer, Alessandra; Simioni, Emanuele; Da Deppo, Vania; Zusi, Michele; Re, Cristina; Lucchetti, Alice; Dami, Michele; Borrelli, Donato; Veltroni, Iacopo Ficai; Tommasi, Leonardo; Aroldi, Gianluca; Mugnuolo, Raffaele; et al.
Highlights: The paper describes the STC channel and its role in the BepiColombo mission. The on-ground performance include the on-ground resolution and detector response. The in-flight performance include the SNR and global coverage of Mercury surface. Conclusions and future steps. Abstract: The Stereo Imaging Channel (STC) is one of the channels of the Spectrometer and Imagers for MPO BepiColombo Integrated Observatory SYStem (SIMBIO-SYS) onboard the ESA BepiColombo mission to Mercury. STC is a double wide-angle camera designed to image each portion of the Mercury surface from two different lines of sights, whose main aim is to provide panchromatic stereo-image pairs required to generate the Digital Terrain Model (DTM) reconstruction. In addition, selected surface areas will be acquired in color. This work presents the expected STC on-ground and in-flight performance describing the preliminary evaluation of some key parameters: the optical performance, the on-ground resolution and detector response, the achievable Signal to Noise Ratio (SNR) for different integration times and observation strategies and the global coverage of panchromatic filters during the entire scientific phase. The estimation of the SNR has been made using the STC radiometric model with Hapke reflectance model for Mercury surface and the SPICE toolkit software. The SPICE toolkit software with kernel for BepiColombo mission has been used also for the estimation of the on-ground pixel dimension and the global coverage all over the mission.